Pengaruh Lingkungan Kerja Internal, Karakteristik Pekerjaan Dan Komitmen Organisasi Terhadap Kinerja Pegawai Dinas Sosial Kabupaten Serdang Bedagai - Firmansyah, Ananda Gusty; Samosir, Suhaila Husna; Lubis, Anggia Sari; Sembiring, Zamaluddin; Safina, Wan Dian (STIM-LPI Makassar, 2024)
The influence of the internal work environment, job characteristics and organizational commitment on employee performance in the Serdang Bedagai Social Service (case study of data collection techniques). Government agencies were established with the aim of providing optimal civil, social and economic rights services to every citizen. Employee performance is influenced by various factors including the internal work environment, job characteristics and organizational commitment. This research aims to explain whether there is an influence of the internal work environment, job characteristics and organizational commitment on employee performance in the Serdang Bedagai Social Service. The population in this study was a sample of 30 people using population techniques. The independent variables are the internal work environment (X1), job characteristics (X2), and organizational commitment (X3) and the dependent variable is employee performance (Y). Data collection methods used were questionnaire and documentation methods. The data analysis method used was percentage description analysis and multiple regression methods.